The Relationship Between Stressful Life Events, Protective Factors, and Depression in Mothers Caring for Young Children in the South Bronx. (5th October 2018) - Hackley, Barbara; Stange, Mia; Kavanaugh, Monica; Aviles, Melanie; Hoffman, Arielle; Zero, Odette; Shapiro, Alan
Abstract : Introduction: Children raised by mothers with maternal depression have poorer physical and mental health, experience more developmental delays, and perform worse in school. The purpose of this cross‐sectional study was to describe predictors of depression in mothers with children aged 5 years of age or younger residing in a low‐income urban community. The specific research questions were to: 1) Describe the prevalence of risk and protective factors associated with depression in mothers in the South Bronx and 2) Determine which social factors are predictive of maternal depression. Understanding factors contributing to maternal depression can improve the development of programs designed to prevent or mitigate maternal depression and its effects on exposed children and families. Methods: A convenience sample of mothers with young children (N = 151) completed an anonymous waiting room survey composed of items from validated questionnaires on depression (PHQ‐2), anxiety (GAD‐2), stress (2‐item scale by Littman), stress management (subscale of the Health Promoting Lifestyle Profile), adverse life events (Modified ACE, CHADIS Potential Stressors), social support (Bright Futures), and father involvement (Turner) in 2012, while receiving care at a Federally Qualified Health Center located in one of the poorest Congressional districts in the United States. Results: On average (SD), women in this study were aged 29.7 (6.4) years and had 2.6 (1.5) children living in their household. Half reported no symptoms of depression or anxiety. Multiple regression models found that 6 out of 12 stressors (childcare, housing, relationship problems, insufficient food, legal problems, and health concerns) accounted for 34% of the variance in depression and anxiety as measured by PHQ‐4 scores (F = 10.3 (6, 118), P < .001). A second regression analysis was calculated predicting maternal depression based on number of stressful life events and protective factors (ability to handle stress, numbers of individuals providing social support, father involvement, and use of stress management techniques) (R 2 = .38, F = 21(3, 98); P < .001). In this model, the number of stressful events and inability to handle stress were predictive of higher symptoms of depression and anxiety, while use of stress management techniques was associated with significantly less symptomatology. Discussion: Programs are needed that address the most salient adverse life events associated with symptoms of depression and anxiety, such as lack of resources, relationship problems, and health concerns. Further, programs should also develop strategies that enhance mothers' ability to cope. These approaches may reduce maternal depression and anxiety, thereby safeguarding the health and well‐being of mothers and children.